Frontmatter (front cover, editorial team, table of contents) - Mohammad Rofiuddin (Fakultas Ekonomi dan Bisnis Islam, Institut Agama Islam Negeri (IAIN) Salatiga, 2020)
Frontmatter of Indonesian Journal of Islamic Economics Research Vol 2 No 1, 2020